2020
DOI: 10.3390/cancers12082196
|View full text |Cite
|
Sign up to set email alerts
|

Two Antagonistic Microtubule Targeting Drugs Act Synergistically to Kill Cancer Cells

Abstract: Paclitaxel is a microtubule stabilizing agent and a successful drug for cancer chemotherapy inducing, however, adverse effects. To reduce the effective dose of paclitaxel, we searched for pharmaceutics which could potentiate its therapeutic effect. We screened a chemical library and selected Carba1, a carbazole, which exerts synergistic cytotoxic effects on tumor cells grown in vitro, when co-administrated with a low dose of paclitaxel. Carba1 targets the colchicine binding-site of tubulin and is a microtubule… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
(58 reference statements)
0
7
0
1
Order By: Relevance
“…They found that low non-saturating concentrations of a MT depolymerizing agent, which enhances catastrophes, promote taxane binding to growing MT tips ( Rai et al, 2020 ). In collaboration with this team, we found that such a mechanism is at work with Carba1, thus explaining the observed synergy ( Peronne et al, 2020 ).…”
Section: Characterization Of Tubulin Drug Binding Sites: Targeting Mi...mentioning
confidence: 64%
See 2 more Smart Citations
“…They found that low non-saturating concentrations of a MT depolymerizing agent, which enhances catastrophes, promote taxane binding to growing MT tips ( Rai et al, 2020 ). In collaboration with this team, we found that such a mechanism is at work with Carba1, thus explaining the observed synergy ( Peronne et al, 2020 ).…”
Section: Characterization Of Tubulin Drug Binding Sites: Targeting Mi...mentioning
confidence: 64%
“…Interestingly, the synergistic effect of Carba1 with PTX on tumor cell viability was also observed in vivo in xenografted mice ( Peronne et al, 2020 ).…”
Section: Characterization Of Tubulin Drug Binding Sites: Targeting Mi...mentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, some drugs, such as our recently described compound Carba1, with low affinity for tubulin, may show a visible depolymerizing effect on tubulin assembly kinetics, but no detectable effect on the microtubular network of interphase cells [30]. The cell-based assay described here is thus complementary to in vitro assays on purified tubulin.…”
Section: Discussionmentioning
confidence: 95%
“…The process of characterizing new MTAs is commonly based on the in vitro analysis of their binding to tubulin (binding assays, competition assays with known agents, affinity measurements [24][25][26][27][28]) as well as on the analysis of their effect on the polymerization of tubulin into microtubules (spectrometric monitoring of the kinetic of tubulin assembly [29,30] or, more recently, tracking of the growth of individual microtubules reconstituted in vitro, by time-lapse fluorescence microscopy [31]). The compounds' characterization is then complemented using tests on cells, such as immunofluorescence analysis of the effect of the compounds on the microtubule network, FACS analysis of their ability to interfere with the cell cycle, and finally analysis of their cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%